Breve storia del Giappone politico-sociale. [Di] N. Konrad, N. Staroselzief [Starosel'cev], F. Mesin [e] E. Jukof [Jukov]. Trad dal russo di F. Sassano (Bari Laterza, 1936)
Biblioteca di Cultura moderna.